2014
DOI: 10.1590/s1984-29612014059
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Community of Cichla kelberi (Perciformes, Cichlidae) in the Três Marias Reservoir, Minas Gerais, Brazil

Abstract: A total of 112 specimens of yellow peacock bass, Cichla kelberi, were collected in the Três Marias Reservoir, upper São Francisco River, State of Minas Gerais, between 2004 and2005. Twelve species of parasites were collected: two species of ectoparasites (the monogenetic Gussevia sp. and the copepod Ergasilus sp.); and ten species of endoparasites, including four species of adult endoparasites: the cestodes Proteocephalus macrophallus and P. microscopicus, and the nematodes: Capillostrongyloides sentinosa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
8
0
2
Order By: Relevance
“…in preferentially piscivorous adult fish (the size reached at first sexual maturity) in the São Francisco River, in the case of C. kelberi (SANTOS-CLAPP & BRASIL-SATO, 2014), and among the Erythrinidae in the present study, make it possible to indicate that the lower level of ingestion of organisms that act as a first intermediate host in the Digenea cycles had negatively affected the chance for fish to act as an intermediate host (other metacercariae, e.g., Clinostomum sp.) and definitive hosts (adult digeneans) for that group of parasites -whose transmission requires the predation of the first or second intermediate host, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…in preferentially piscivorous adult fish (the size reached at first sexual maturity) in the São Francisco River, in the case of C. kelberi (SANTOS-CLAPP & BRASIL-SATO, 2014), and among the Erythrinidae in the present study, make it possible to indicate that the lower level of ingestion of organisms that act as a first intermediate host in the Digenea cycles had negatively affected the chance for fish to act as an intermediate host (other metacercariae, e.g., Clinostomum sp.) and definitive hosts (adult digeneans) for that group of parasites -whose transmission requires the predation of the first or second intermediate host, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…had already been found in Leporinus friderici (Bloch, 1794) in the upper Paraná river by Takemoto et al (2009 (Moravec, 1998). In the upper São Francisco river, and Santos-Clapp & Brasil-Sato (2014) reported occurrences of these larvae in the carnivorous fish Cichla kelberi Kulander & Ferreira, 2006). In the present study, these larvae were also found in A. fasciatus, thus showing that this fish acts as an intermediate host for these parasites.…”
Section: Resultsmentioning
confidence: 97%
“…and Goezia sp. in A. fasciatus enlarges the list of hosts in the São Francisco river, especially given that occurrences of these species had already been identified in several families of fish in the upper São Francisco river (BRASIL-SATO, 2003;SANTOS-CLAPP & BRASIL-SATO, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Procamallanus (S.) inopinatus is a generalist nematode that has been found in a number of fish species from the São Francisco River basin (BRASIL-SATO, 2003;SANTOS-CLAPP & BRASIL-SATO, 2014) and in several freshwater ecosystems as well (MORAVEC, 1998). This helminth species parasitizes M. maculatus from the Paraná River, M. lippincottianus from the Paraná River and a tributary of the Amazon River basin (MOREIRA et al, 2009;HOSHINO & TAVARES-DIAS, 2014), and M. hypsauchen from the Jari River, Brazilian Amazon (OLIVEIRA et al, 2015).…”
Section: Discussionmentioning
confidence: 99%